Using data to improve the care of people with diabetes across Oxfordshire. (6th February 2020) - Rea, Rustam D; Lumb, Alistair; Tan, Garry D; Owen, Katharine; Thanabalasingham, Gaya; Latif, Amar; Swan, Paul; Scott, James; Jones, David; Gillott, Emily; Smith, Rosemary Honour
Abstract: Data from GP practices and hospital trusts have long been used to understand the quality of care received by people with diabetes. However, annual data collection is too infrequent to see what difference rapid changes in practice make to diabetes care. We developed a diabetes dashboard modelled on the National Diabetes Audit (NDA), which provided monthly updates on key care components. The data were displayed at both individual GP level as well as at a Locality level (now called primary care network [PCN] level) and clinical commissioning group (CCG) level. Discussion about the dashboard was incorporated into regular GP practice visits by diabetes consultants and community diabetes specialist nurses which occurred twice a year to nearly every GP practice in the CCG. Twice‐yearly Locality meetings also reviewed the data at Locality level and provided a forum for sharing 'best practice'. Over the last two years significant improvements have been seen, particularly in the achievement of the eight key care processes and the attendance at structured education within one year of diagnosis. The diabetes dashboard has been integral in the improvement of care for people with diabetes in Oxfordshire. It continues to evolve with data now displayed at PCN level and ongoing work to align the dashboard with the NDA coding. The dashboard was most effective when used within the context of supportive clinical engagement.